Why do firms use fixed-term contracts? - Pedro Portugal; José Varej\~ao (Institute for the Study of Labor (IZA), 2009)
Temporary forms of employment account for a variable but never trivial share of total employment in both the U.S. and in Europe. In this article we look at how one specific form of temporary employment - employment with fixed-term contracts - fits into employers' hiring policies. We find that human capital variables (schooling, skills and employer-provided training) as measured at the levels of the worker and the workplace are important determinants of the employers' decisions to hire with fixed-term contracts and to promote temporary workers to permanent positions. Those employers that hire more with fixed-term contracts are also those that are more likely to offer a permanent position to their newly-hired temporary employees. Our results indicate that fixed-term contracts are used as mechanisms for screening workers for permanent positions.
urn:nbn:de:101:1-200910085849
Keywords: J23; J41; 330; Fixed-term contracts; adjustment costs; labor demand; Befristeter Arbeitsvertrag; Arbeitsnachfrage; Humankapital; Anpassungskosten; Theorie; Portugal